DIGITAL STORYTELLING TO SUPPORT YOUNG LEARNERS’ ENGLISH VOCABULARY DEVELOPMENT - Lailatul Maya; Sri Sumarni; Muchlas Suseno (Jurnal Bahasa Lingua Scientia, 2022)
Due to the explosive growth of technology, teachers are required to integrate technology into the classroom to engage learners who are regarded as digital natives. Digital storytelling can be an alternative medium for vocabulary learning. This case study examined how young learners perceived the implementation of digital storytelling during vocabulary learning. In-depth interviews and closed-ended questionnaires were employed to investigate the use of digital storytelling in the classroom. The sample of the study recruited 23 fifth-grade learners from an elementary school in Tuban, East Java. The qualitative data from the interviews and questionnaires of the young learners revealed that they considered digital storytelling more engaging, fascinating, and motivating for improving their vocabulary development. As a result, EFL teachers are recommended to deliver appropriate digital storytelling to young learners in order to teach vocabulary and support their vocabulary development.